Association of urinary metabolites with radiographic progression of knee osteoarthritis in overweight and obese adults: an exploratory study. Issue 8 (August 2016) - Loeser, R.F.; Pathmasiri, W.; Sumner, S.J.; McRitchie, S.; Beavers, D.; Saxena, P.; Nicklas, B.J.; Jordan, J.; Guermazi, A.; Hunter, D.J.; Messier, S.P.
Summary: Introduction: Metabolic factors may contribute to osteoarthritis (OA). This study employed metabolomics analyses to determine if differences in metabolite profiles could distinguish people with knee OA who exhibited radiographic progression. Methods: Urine samples obtained at baseline and 18 months from overweight and obese adults in the Intensive Diet and Exercise for Arthritis (IDEA) trial were selected from two subgroups ( n  = 22 each) for metabolomics analysis: a group that exhibited radiographic progression (≥0.7 mm decrease in joint space width, JSW) and an age, gender, and body mass index (BMI) matched group who did not progress (≤0.35 mm decrease in JSW). Multivariate analysis methods, including orthogonal partial least square discriminate analysis, were used to identify metabolite profiles that separated progressors and non-progressors. Plasma levels of IL-6 and C-reactive protein (CRP) were evaluated as inflammatory markers. Results: Multivariate analysis of the binned metabolomics data distinguished progressors from non-progressors. Library matching revealed that glycolate, hippurate, and trigonelline were among the important metabolites for distinguishing progressors from non-progressors at baseline whereas alanine, N, N-dimethylglycine, glycolate, hippurate, histidine, and trigonelline, were among the metabolites that were important for the discrimination at 18 months. In non-progressors, IL-6 decreased from baseline to 18 months while IL-6 was unchanged in progressors; the change over time in IL-6 was significantly different between groups. Conclusion: These findings support a role for metabolic factors in the progression of knee OA and suggest that measurement of metabolites could be useful to predict progression. Further investigation in a larger sample that would include targeted investigation of specific metabolites is warranted.